Use of Gabapentin in Management of Acute Pain After Surgery: Review of Literature - Amir Hossein Eskandari; Sadaf Alipour (Tehran University of Medical Sciences, 2019)
Background and goals: Breast surgery is one of the most common surgical operations performed worldwide as well as in Iran. Acute postoperative pain is managed by different therapeutic modalities in these procedures, and opioid are the most frequently used option; however their adverse consequences imposes restriction of use.  The goal of this article is to review the effects of gabapentin on postoperative pain and opioid use in breast surgeries. Materials and Method:  PubMed, Ovid Medline, and Scopus databases from 2000 to 2019; as well as Google scholar, first 350 results, were searched for all clinical trials and review articles about the subject, using various related keywords. Sixty-two articles were reviewed by 2 researchers and finally data from 22 papers were gathered and assessed. Results: This review demonstrates that gabapentin is effective in reducing acute postoperative pain after operations of the breast. Also, rate of opioid consumption, an important objective in the period after surgery, is reduced by use of opioids. Conclusion: This study prompts the effectiveness of gabapentin in controlling postoperative pain in breast operations; since this drug is very seldom used for this purpose in our country, we propose that medical staff consider it as a powerful option after breast procedures.